DOL- Distance and Online Education in the Wake of NEP 2020 (International Journal of Food and Nutritional Sciences, 2023)
The age we are living in is of digitalization and Information and Communication Technology (ICT). This era is known as the advent and rigorous adaptation of novel technologies in various spheres of human life. The widespread use of the internet brought a shift in basic assumptions about education. Therefore, the role of classroom as the only place for imparting traditional formal education, access to information, and the activity of knowledge generation is seen in a challenging state. The growing use of the internet for learning, especially during the period of Covid-19 followed by lockdowns, is turning out to be supplementary for classroom teaching and learning. Eventually, it has brought education outside of the exclusive university gates and into everyone's hands.In the light of this radical transformation, Online and Distance education is contributing tremendously to the creation, accessibility, and delivery of knowledge in the altering knowledge economy and knowledge society. The New Educational Policy i.e., (NEP 2020) of India is going to be in favor of rapid spread of Online and Distance education via many public, private, and foreign universities and colleges. Through this mode of learning, NEP seeks strengthening and guaranteeing Access, Equity, Quality and Affordability as the very base of 21st century modern education system of India. The present research paper is a modest attempt to throw a light on the evolution of Distance and Online education in India and its remarkable growth. The researcher also seeks to explore the merits and demerits of these new modes of education and the role of NEP 2020 in its future existence.